Physical Performance of West Java Soccer Athletes during February to December 2012 - Army Zaka Anwary; Ambrosius Purba; Tertianto Prabowo (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Soccer is one of the sports included in the 18th National Sports Week (Pekan Olahraga Nasional, (PON) 2012, in Riau. Soccer requires a good physical condition to perform various football techniques such as running, shooting, dribbling, tackling, sliding, throw-in and heading. A good physical component can be achieved through a well-rounded program in accordance to the periodization training program. This study was conducted to describe the physical performance of the West Java’s football athletes in order to develop periodization training program and to predict the athletes’ performance.Methods: A descriptive study was carried out on 23 West Java’s football athletes using secondary data from West Java’s KONI sports medicine team test reports during the period of February to December 2012. The variables in this study were 7 predominant physical components in football as follows: muscle strength, muscle endurance, speed, agility, flexibility, explosive leg muscle power, and general endurance (VO2 max). All components were categorized asInsufficient, Fair, Good, Excellent, and Perfect compared to the central KONI standards.Results: The leg muscle strength, abdominal muscle endurance, speed, agility of all athletes were not considered perfect. Not one of the components was above 50% which was the excellent category. Only Arm and shoulder endurance (56.5%), speed (68.18%), and leg muscle power (52.17%) were in good category. The most of the results regarding the athletes’ leg muscle strength was categorized as fair. All results in the abdominal endurance were in insufficient category.Conclusion: Not all physical performance components are achieved perfectly by all of the football athletes.Keywords: Athletes, football, physical performance DOI: 10.15850/amj.v2n1.442